2014
DOI: 10.1186/1471-2334-14-191
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes in critical patients with hemorrhagic fever with renal syndrome

Abstract: BackgroundHemorrhagic fever with renal syndrome (HFRS) has become an important public health concern because of the high incidence and mortality rates, and limited treatment and vaccination. Until now, clinical studies on characteristics and outcomes in critical patients with HFRS have been limited. The aim of this study was to observe the clinical characteristics and cumulative proportions surviving and explore the predictive effects and risk factors for prognosis.MethodsA detailed retrospective analysis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 26 publications
2
49
1
Order By: Relevance
“…There was also a positive correlation observed between elevated plasma sCD163 levels and BUN and Cr levels, which was previously shown to predict kidney dysfunction in HFRS patients [25] . This suggests that sCD163 might be involved in renal dysfunction.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…There was also a positive correlation observed between elevated plasma sCD163 levels and BUN and Cr levels, which was previously shown to predict kidney dysfunction in HFRS patients [25] . This suggests that sCD163 might be involved in renal dysfunction.…”
Section: Discussionsupporting
confidence: 72%
“…According to the laboratory parameters and symptoms, such as body temperature, hemorrhage, edema, blood pressure and urine volume, the degree of HFRS disease severity was classified into the four clinical types, as formerly described [25] . These types were classified as: (1) mild, which included mild renal failure without an obvious oliguric stage and hypotension; (2) moderate, which included evident uremia, effusion (bulbar conjunctiva), hemorrhage (skin and mucous membrane) and acute renal failure with an obvious oliguric stage; (3) severe, which included severe uremia, effusion (bulbar conjunctiva and either pleura or peritoneum), hemorrhage (skin and mucous membrane), and acute renal failure with oliguria (a urine output of 100–500 ml/day) for ≤5 days or anuria (a urine output of <100 ml/day) for ≤2 days; and (4) critical, which were cases with one or more of the following symptoms compared with the severe patients: refractory shock (≥2 days), visceral hemorrhage, heart failure, pulmonary edema, brain edema, severe secondary infection and severe acute renal failure with oliguria (a urine output of 50–500 ml/day) for >5 days or anuria (a urine output of <100 ml/day) for >2 days, or a blood urea nitrogen level of >42.84 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…According to the HFRS criteria of clinical classification [ 7 ], the severity of HFRS was classified into four types: (1) mild, defined as patients who had kidney injury without oliguria and hypotension; (2) moderate, defined as patients who had uremia, effusion (bulbar conjunctiva), hypotension, hemorrhage (skin and mucous membranes), and AKI with typical oliguria; (3) severe, defined as patients who had severe uremia, effusion (bulbar conjunctiva and either peritoneum or pleura), hemorrhage (skin and mucous membranes), hypotension, and AKI with oliguria (urine output of 50–500 mL/day) for ≤5 days or anuria (urine output of <100 mL/day) for ≤2 days; and (4) critical, defined as patients who usually had one or more of the following complications compared with the severe patients: refractory shock (≥2 days), visceral hemorrhage, heart failure, pulmonary edema, brain edema, severe secondary infection, and severe AKI with oliguria (urine output of 50–500 mL/day) for >5 days or anuria (urine output of <100 mL/day) for >2 days. Considering the clinical conditions that a majority of the survival patients had been discharged before the convalescent phase and the degree of acute kidney injury (AKI) that was still severe during the early stage of the diuretic phase, the acute stage was defined as the period that included the febrile, hypotensive, and oliguric phases and the early three days of the diuretic phase in this study, and the convalescent stage was defined as the diuretic and convalescent phase except the early three days of the diuretic phase.…”
Section: Methodsmentioning
confidence: 99%
“…Hubei Province is known as the "land of a thousand lakes". The climate and ecological conditions in Hubei Province provide an ideal habitat for rodents [45]. Xiao et al demonstrated that moist environments are help for the vitality and infectivity of Hantaan virus and the distribution of rodents [41].…”
Section: Discussionmentioning
confidence: 99%